Histological studies on small bulb flower crops - Kohut, I.; Gracza, P.; Tar, T. (International Journal of Horticultural Science, 2005)
Investigations were done in order to obtain more information on the histological structure of bulbs of Allium moly, Allium sphaerocephalon, Muscari armeniacum and corms of Crocus sativus. While starch grain were found in the bulb of Muscari armeniacum, fluid nutrient content were shown in Allium species. Narrow and fleshy scales were found in the bulbs of Muscari. Histological characteristics of Allium moly and Allium sphaerocephalon showed a closer relationship with corms than with the bulbs. To clarify this question, further investigations are needed (Bailey, 1942; Larson, 1980).